An ecological crisis of reason: using creative and arts-based research methods for exploring affective-emotional life and just transitions - Clifton Evers (Global Social Challenges Journal)
In 2017, the Swedish parliament committed to making the country fossil-free by 2045, prompting an exploration of experiences and perceptions of transition in three cities hosting carbon-intensive industries – steel, cement and petrochemicals, which currently top the list of Sweden’s industrial emitters. From 2019 to 2024, a Swedish–UK research team employed conventional qualitative methods to gather insights from various stakeholders, including industry, municipal actors, and residents, supplemented by arts-based research methods for co-creating data on affective-emotional life in transition towns. This article argues that arts-based research serves as a valuable tool for accounting for and understanding affective-emotional life in frontline transition towns. The arts-based research (ABR) challenges prevailing technocratic and rational frameworks, aligning with ecofeminist Val Plumwood’s call to address the ‘ecological crisis of reason’ that serves to inhibit achieving sustainable futures. The primary value of this article lies in its contribution to the development and refinement of ABR within the context of just transition studies that I argue can help add citizen perspectives and consideration of affective-emotional life to the just transition discourse.